New route to 1-thia-closo-dodecaborane(11), closo-1-SB11H11, and its halogenation reactions. The effect of the halogen on the dipole moments and the NMR spectra and the importance of spin-orbit coupling for the 11B chemical shifts - Machácek, Jan; Plesek, Jaromír; Holub, Josef; Hnyk, Drahomír; Vsetecka, Václav; Císarová, Ivana; Kaupp, Martin; Stíbr, Bohumil (Dalton transactions (Cambridge, England, 2006)
Reaction between nido-B10H14 (1) and elemental sulfur in CHCl3 in the presence of Et3N at room temperature, followed by treatment with Et3N.BH3 at 170-190 degrees C, resulted in the isolation of closo-1-SB11H11 (2) in 50% yield. Selected electrophilic halogenation reactions of compound led to the isolation of a series of monohalogenated derivatives of general constitution 12-X-closo-1-SB11H10 (12-X-, where X = Cl, Br, and I). The structures of 12-Cl- and 12-I- were determined by an X-ray diffraction analysis and the structures of all compounds were geometry optimised at the RMP2(fc)/6-31G* level. The constitution of all compounds is consistent with the results of mass spectrometry and multinuclear (1H and 11B) spectroscopy complemented by two-dimensional [11B-11B]-COSY and 1H{11B(selective)} NMR measurements. Experimental 11B chemical shifts generally show acceptable agreement with theoretical values calculated by GIAO methods, but spin-orbit coupling must be included for nuclei bearing heavy-atom substituents such as Br or I. The dipole moments determined for the B12-X bonds show similarities to those of aliphatic C-X bonds and confirm unambiguously the B12 --> S dipole moment orientation in the SB11 cage.